Choice criteria for private tertiary programs at a private higher education institution / Nurlida Ismail...[et al.] - Ismail, Nurlida; Leow, Yen Mee; Chen, Chee Hoong (ACRULeT, Faculty of Education & UiTM Press, 2007)
The objective of this study is to examine key determinants that influence students’ choice in selecting a program. The theoretical framework was adapted from Chapman’s (1981) and Cubillo, Sanchez and Cervino’s (2006) models. Our study of students’ choice criteria was conducted using the survey questionnaire method and a five-point Likert scale was employed. The sample for the testing and refinement process consisted of 299 first year tertiary students from across all three programs in a private higher education institution. All our hypotheses are supported by Multiple Linear Regression analysis. The results indicated that program evaluation is the most significant factor that influences students’ program choice. This is followed by the college is effort to communicate with students and level of educational aspiration. However, it was found that significant persons have the least influence on students’ program choice.